A world revision of the bee fly tribe Usiini (Diptera, Bombyliidae) Part 2: Usia sensu stricto - Gibbs, David (Zootaxa, 2014)
This is the second part of a world revision of the genera Usia Latreille and Parageron Paramonov, of the tribe Usiini Becker, and covers the pale-haired species, the Usia sensu stricto group. Usia sensu stricto as defined here contains 24 species of which 16 species fall into two monophyletic groups, the U. lata group with 10 species and the U. florea group with six species. Eight species cannot be placed in either of these two groups, four of them form two pairs of sibling species while the remaining four species have no clear affinities. Of the 25 formerly available names that belong in Usia sensu stricto, U. putilla Becker stat. rev., previously synonymised under U. angustifrons, is reinstated as a full species. U. sicula Egger syn. nov., is synonymised under U. manca Loew, U. anus Becker syn. nov., is synonymised under U. vestita Macquart and U. claripennis Macquart syn. nov., is synonymised under U. atrata (Fabricius). Usia vicina Macquart, formerly placed as a synonym of U. atrata, is shown to be a junior synonym of U. aenea Rossi. Five new species are described, U. anatoliensis sp. nov., U. annetteae sp. nov., U. greatheadi sp. nov., U. maghrebensis sp. nov. and U. cornigera sp. nov. Both the male and female genitalia are illustrated in detail for 21 species, female only in the cases of U. calva Loew and U. notata Loew and male only for U. incognita Paramonov.